Outcomes in Deep Inferior Epigastric Perforator Flap and Implant-Based Reconstruction: Does Age Really Matter?. (10th January 2018) - Kuykendall, Lauren V.; Zhang, Angie; Tugertimur, Bugra; Bijan, Sara; Agoris, Corin; Kumar, Ambuj; Dayicioglu, Deniz
Despite the growing elderly population, there is limited research specific to this demographic concerning breast reconstruction (BR). Lack of evidence-based BR recommendations in older populations may contribute to misconceptions and subsequent underutilization of BR, especially autologous BR. Patients who received either deep inferior epigastric perforator (DIEP) flap BR or tissue expander/implant (TE/I) BR by a single surgeon between July 2011 and July 2015 were surveyed postoperatively by using the psychometrically validated BREAST-Q questionnaire to determine patient satisfaction. Patients were categorized into younger and older cohorts based on median age (55 years) and further stratified based on the type of reconstruction. Of the 311 patients surveyed, 95 patients responded (31% response rate). Overall, younger patients (<55 years old, n = 42) compared with older patients (≥55 years old, n = 53) had significantly higher satisfaction with their outcome (mean difference [MD] 12.06; 95% confidence interval [CI]: 0.96-23.15; P = 0.034). In the TE/I group (n = 58), younger patients had significantly higher satisfaction with breasts (MD: 14.17; 95% CI: 2.58-25.75; P = .017) and outcome (MD: 18.25; 95% CI: 3.95-32.5; P = .010) with fewer complications (odds ratio [OR]: 3.29; 95% CI: 1.37-7.86; P = .010). In the DIEP flap group (n = 55), there was no significant difference inr any of the satisfaction outcomes between younger and older patients. Younger patients tend to be more satisfied and demonstrate fewer complications with implant-based BR. In contrast, both younger and older patients undergoing abdominally based autologous BR were equally satisfied with comparable outcomes.